Economy and the Family Belief: Understanding the Idea and the Consequence - Hifzhan F. Thousani; Netty Lisdiantini; Hendrick Hernando; Farida T. Hastuti; Niza Nurmalasari (Universitas Muhammadiyah Palu, 2023)
The concept of the family has been established in Indonesian economic theory ever since the republic's declaration. There is controversy over how the family principle should be employed as the foundation of the Indonesian economy, though the notion is still not comprehended. Thus, the aim of this research is to describe in what way the family principle in Indonesia’s Economy has been regarded and understood in order to avoid misconception or multi-interpretations to comprehend it. Qualitative approach which is based on literary studies is used in this research. This approach considers being appropriate for studies in the environment of economic theory since researchers attempt to comprehend the understanding and thoughts of significant figures in the Indonesia economy. The findings show that there are two critical and similarly important elements of the family principle to comprehensively understand the concept namely cooperation and competition. The research suggests that both concepts had been integrated into the family principle as competition, while all economic institutions recognized by the constitution concurrently compete and cooperate.